A Brief Survey on Nature Inspired Metaheuristic and Hybrid-Metaheuristic Optimization Algorithm - Wunnava, Aneesh; Kumar Naik, Manoj (International Journal of Engineering and Technology, 2018)
The human brains are the ultimate model optimization algorithm, but they are complex in nature. The small microorganism and mammals other than human are do foraging and reproduce to survive in the world by optimizing in a small environment. This leads to a researcher to investigate their lifestyle and foraging behavior in a mathematical model coined as the nature-inspired optimization algorithm. In this brief survey on nature-inspired optimization algorithm related to metaheuristic and hybrid-metaheuristic, we try to show some recent development that is widely used nowadays.Â